Abl activation regulates the dissociation of CAS from cytoskeletal vimentin by modulating CAS phosphorylation in smooth muscle - Jia, Li (American Physiological Society, 2010)
Abl is a nonreceptor tyrosine kinase that is required for smooth muscle contraction. However, the mechanism by which Abl regulates smooth muscle contraction is not completely understood. In the present study, Abl underwent phosphorylation at Tyr412 (an index of Abl activation) in smooth muscle in response to contractile activation. Treatment with a cell-permeable decoy peptide, but not the control peptide, attenuated Abl phosphorylation during contractile stimulation. Treatment with the decoy peptide did not affect the association of Abl with the cytoskeletal protein vinculin and the spatial location of vinculin in smooth muscle. Inhibition of Abl phosphorylation by the decoy peptide attenuated the agonist-induced phosphorylation of Crk-associated substrate (CAS), an adapter protein participating in the signaling processes that regulate force development in smooth muscle. Additionally, previous studies have shown that contractile stimulation triggers the dissociation of CAS from the vimentin network, which is important for cytoskeletal signaling and contraction in smooth muscle. In this report, the decrease in the amount of CAS in cytoskeletal vimentin in response to contractile activation was reversed by the Abl inhibition with the decoy peptide. Moreover, force development and the enhancement of F-actin-to-G-actin ratios (an indication of actin polymerization) upon contractile activation were also attenuated by the Abl inhibition. However, myosin phosphorylation induced by contractile activation was not affected by the inhibition of Abl. These results suggest that Abl regulates the dissociation of CAS from the vimentin network, actin polymerization, and contraction by modulating CAS phosphorylation in smooth muscle.